Analysis of Curricular Adaptations and Teacher Training in the Area of Visual Disability - Picón, Gerardo Armando (Journal of Education and Training, 2024)
The objective was to evaluate the process of curricular adaptation considering the visual disability of the students of the school institutions of Region 00-17 of the La Encarnación District in Paraguay. It was a non-experimental, quantitative, descriptive cross-sectional study. The sample consisted of 69 teachers, selected in a non-probabilistic, intentional, and voluntary manner. The survey technique was used through a questionnaire, validated by experts, and applied through links on the institutions' platforms. The data were quantitatively processed with Microsoft Excel 2010. As results we found the usefulness of educational strategies for students with visual disabilities, the consideration that adapted furniture and folding tables were beneficial stood out. Most teachers pointed out the lack of adequacy of furniture and infrastructure. The training received to teach blind children found aspects such as special didactics, reading and writing in Braille, extremely useful. They expressed the need to receive more training. Significant Curriculum Adaptations were considered extremely useful. The importance of respect, tolerance, and general awareness around special education was highlighted. Regarding inserting children with blindness problems into the official educational system, most teachers agreed with being active participants in the learning process. We conclude on the critical need for comprehensive teacher preparation, the availability of adequate resources, the implementation of inclusive strategies, and the promotion of positive attitudes to guarantee the academic success.